Time course and reaction types of serum IGF-1 and its relationship to BMI and leptin regarding inpatients with anorexia nervosa - Hellwig-Walter, Christiane; Brune, Maik; Schellberg, Dieter; Buckert, Magdalena; Wesche, Daniela; Cuntz, Ulrich; Friederich, Hans-Christoph; Wild, Beate (Growth hormone & IGF research, 2022)
Objective - Anorexia nervosa (AN) is a severe mental disorder that is characterized by restriction of energy intake, low weight, and endocrine abnormalities. One of the known endocrine changes in relation to underweight is in the GH/IGF-I axis. The aim of the study was (a) to investigate longitudinal characteristics of the IGF-I-change during therapy and weight gain in adult AN, (b) to determine relationships between IGF-I and leptin, (c) to characterize patients with weak and pronounced hormonal reactions to underweight. - Design - Data was assessed from 19 AN patients. Over the first two months, serum IGF-I concentrations were assessed on a weekly basis; thereafter on a monthly basis. The trend of IGF-I values over time was analyzed using individual growth models. - Results - In total, n = 177 IGF-I measurements were analyzed. IGF-I increased significantly dependent on BMI (slope = 20.81, p < 0.001), not modulated by duration of disease. The increase in IGF-I was significantly related to the increase in leptin concentrations over time (slope = 15.57, p < 0.001). Patients with a weaker hormonal reaction to underweight were significantly older compared to patients with a pronounced hormonal reaction (t(17) = 3.07, p = 0.007). - Conclusions - During treatment, IGF-I change is clearly related to BMI as well as to leptin. Age appears to be associated with the IGF-I response to underweight.
Gesehen am 27.07.2022